The baseball glove - Jenemann, David, 1971- author.
1 online resource (172 pages)
Keywords: The baseball glove is a ubiquitous item, a crucial piece of equipment in the game of baseball, and it offers the opportunity to examine the production of material culture and social practice at numerous levels. Where and how is a glove made, and how does its manufacture square with the narratives surrounding its place in American cultural life? What are the myths, superstitions, and beliefs surrounding its acquisition, care, use, and significance? How does a glove function as the center of a web of cultural practices that illustrate how individuals relate to a consumer good as a symbol of memory, personal narrative, and national identity? How do the manufacturers of baseball gloves draw upon, promote, and in some sense create these practices? How do these practices and meanings change in other national and cultural contexts? The Baseball Glove offers students the opportunity to examine these questions in an engagingly written and illustrated book that promotes hands-on interaction with a quintessential item of material culture. At the same time, the book gives students the space for critical self-reflection about the place of material goods like sporting equipment in their lives, and it provides the chance to learn different methodological approaches to studying everyday objects.